Determinant of school children’s nutritional status in Musi Rawas district - Tita Priyanka Putri; Rico Januar Sitorus; Anita Rahmiwati (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: The phase of school-age children really needs nutritious food intake to support their growth and development. Consumption of diverse foods can complement the advantages of the nutritional arrangement of other types of food so that a balanced nutritional input is obtained.Objectives: The purpose of this study was to analyze the determinant of school children’s nutritional statusMaterials and Methods: This study used a cross-sectional design. Data collection was carried out using cluster random sampling to select sub-district and school, simple random sampling techniques to select respondents. The sample in this study was 208 respondents. Data Characteristic (age, gender, pocket money, parental education and income, history of infectious diseases) and nutritional knowledge was collected using questionnaires independently, food consumption diversity was measured using Individual Dietary Diversity Score (IDDS), and nutritional status was measured using CDC 2000. Chi square test was used to analyze association between two categorical variables and multivariate analysis was carried out using risk factor models to determine the impact of multiple potential risk factors on nutritional status.Results: The results of respondents on the dietary diversity variable were diverse at 84.6%. There was a relationship between dietary diversity (p=0.021), nutritional knowledge (p=0.02), history of infectious diseases (p=<0.001) to nutritional status but there was no relationship between pocket money, parents education, parents income, parents occupation and nutritional status of elementary school children. The results of the multivariate analysis indicated a significant association between food consumption diversity and children’s nutritional status (p = 0.021). This relationship continued to be significant even after adjusting for nutritional knowledge, parental income, and previous infectious diseasesConclusion: The diversity of children’s food consumption plays a significant role in shaping their nutritional status, even when other factors such as nutritional knowledge, parental income, and history of infectious diseases are taken into accountKeywords: Children; dietary diversity; nutritional status; school children